Penguasaan leksikon Bahasa Indonesia siswa Taman Kanak-Kanak Tarakanita Bumijo - Windiarti, Lucia; Setiawan, Teguh (LingTera, 2017)
Penelitian ini bertujuan untuk mendeskripsikan mengenai 3 masalah, yaitu: (1) jenis kata, (2) variasi makna kata, dan (3) ragam bahasa Indonesia yang dikuasai siswa TK Tarakanita Bumijo. Penelitian ini merupakan penelitian deskriptif kualitatif. Metode analisis data yang digunakan adalah metode kualitatif yang dilakukan dengan cara inventarisasi, identifikasi, klasifikasi, dan deskripsi. Penelitian menghasilkan tiga simpulan. Pertama, jenis kata bahasa Indonesia yang dikuasai siswa TK Tarakanita Bumijo meliputi nomina, verba, adjektiva, adverbia, pronomina, numeralia, dan kata tugas. Kedua, variasi makna kata bahasa Indonesia yang dikuasai oleh TK Tarakanita Bumijo meliputi sinonimi, antonimi, hiponimi, lugas, dan kias. Ketiga, ragam bahasa Indonesia yang dikuasai oleh siswa TK Tarakanita Bumijo meliputi ragam santai dan formal. Indonesian lexicon mastery by Tarakanita Bumijo Kindergarten students AbstractThe purpose of this study is to describe the three issues, namely: (1) the word classes, (2) variations in the meaning of the word, and (3) varieties of Indonesian languages that were mastered by Tarakanita Bumijo This research was qualitative descriptive research. The data collection method was recording and interview. The analysis methods were qualitative by the doing inventory, identifying, classifying, and describing. The research generates three conclusions. First, the word classes of Indonesian language mastered by Tarakanita Bumijo Kindergarten students are noun, verb, adverb, pronoun, number, and task words. Second, the variation of meanings of words of Indonesian mastered by Tarakanita Bumijo Kindergarten students is the synonym, antonym, hyponym, lugas, and idiom. Third, the styles of the language of Indonesian mastered by Tarakanita Bumijo Kindergarten students are informal and formal styles.